Kontrak Sosial dan Pemilihan Umum - Sanit, Arbi (Jurnal Penelitian Politik, 2004)
Social contract is a conception about new p ow e r relationship between elite and people which is formulated in order to fulfill a d em an d fo r p o litica l renewal which is need a continuity, not stagnation nor deterioration. We need to reconstruct any aspect o f social contract theory in order to understand about social contract relevance with general election. The general election as a contract social guaranteed rights and obligation ofthe voters and the leaders. The contract mechanism between voters and political candidate is related by trust. The object o f trust itse lf in general election is morality. The political contract consistency based on trust is afoundation fo r building a State as a moral entity, which is made by morally human being.